Understanding the Linkages Between Financial Markets and Sustainable Economic Development - Maharajabdinul, Maharajabdinul (Advances in Economics & Financial Studies, 2024)
Purpose: This study investigates the interplay between financial markets and sustainable economic development, aiming to clarify how financial activities influence sustainability goals and vice versa. Research Design and Methodology: The research utilizes a multidisciplinary approach, drawing insights from economics, finance, environmental studies, sociology, and political science. A comprehensive literature review was conducted to synthesize existing knowledge and identify research gaps, focusing on theoretical and empirical studies without primary data collection. Findings and Discussion: Findings reveal that financial markets are crucial for capital allocation and resource mobilization but can also lead to environmental degradation, social inequality, and systemic risks. The study emphasizes the significant role of regulatory frameworks and institutional arrangements in determining how financial markets affect sustainability outcomes, highlighting the need for integrated reforms, regulatory measures, and stakeholder collaboration. Implications: The study underscores the importance of aligning financial incentives with sustainability objectives and enhancing the resilience of financial systems. It calls for stronger partnerships among stakeholders and suggests that further research is needed to explore innovative financial mechanisms that promote sustainable development and assess the long-term impacts of financial practices on sustainability. These insights are valuable for policymakers, practitioners, and scholars navigating the finance-sustainability nexus.